Users' perspective on rehabilitation interventions for young adult cancer survivors: A group concept mapping study. (11th October 2022) - Aagesen, Maria; Pilegaard, Marc Sampedro; Hauken, May Aasebø; Wæhrens, Eva Elisabet Ejlersen; la Cour, Karen
Abstract: Objective: We aim to identify and prioritise rehabilitation interventions to strengthen participation in everyday life for young adult cancer survivors (YACS) between 18 and 39 years, involving the perspectives of YACS and relevant stakeholders. Methods: A group concept mapping study was conducted in Denmark from 2019 to 2020. Online, participants generated and sorted ideas followed by rating their importance. Multidimensional scaling followed by hierarchical cluster analyses were applied to generate a cluster rating map of the prioritised interventions, which participants validated at a face‐to‐face meeting. Finally, a concluding conceptual model of prioritised rehabilitation intervention for YACS was developed. Results: The study involved 25 YACS, three family members and 31 professionals working with YACS. The conceptual model included 149 ideas classified into eight intervention components created by the participants: (1) Treatment and possibilities within the social and healthcare system, (2) Rights and Finance, (3) Education and Work, (4) Psychological problems, (5) Body and Everyday Life, (6) Peer‐to‐peer, (7) Sexuality and Relationships and (8) Family and Friends. All components were rated equally important, whereby 17 ideas across the eight components were rated very important. Conclusion: This study indicates that rehabilitation of YACS should be composed of eight equally important intervention components requiring an interdisciplinary approach.